Revision of the Australian bee fly genus Meomyia Evenhuis, 1983, with description of three new species (Bombyliidae, Bombyliinae, Bombyliini) - Li, Xuankun; Yeates, David K. (Zootaxa, 2020)
The endemic Australian bee fly genus Meomyia Evenhuis is revised, including six described species and three newly described: Meomyia hortorum sp. nov., Meomyia kochae sp. nov., Meomyia melanocincta sp. nov. Bombylius tetratrichus Walker is excluded from Meomyia and placed in Dissodesma Bowden & Li. Meomyia is characterised by the slender and elongate antennal flagellum, and the black abdominal band and dense black tuft on apex of abdomen. A key to species of Meomyia is provided. Species are found in southern Australia.